Unilateral Cochlear Nerve Deficiency in Children. Issue 2 (15th May 2013) - Clemmens, Clarice S.; Guidi, Jessica; Caroff, Aviva; Cohn, Samuel J.; Brant, Jason A.; Laury, Adrienne M.; Bilaniuk, Larissa T.; Germiller, John A.
Abstract : Objective: Cochlear nerve deficiency (CND) is increasingly diagnosed in children with sensorineural hearing loss (SNHL). We sought to determine the prevalence of CND, its imaging characteristics, and correlations with audiologic phenotype in children with unilateral SNHL. Design: Case series with chart review. Setting: Tertiary pediatric hospital. Subjects/Methods: In 128 consecutive children with unilateral SNHL who underwent high‐resolution magnetic resonance imaging, the diameters, area, and signal intensity of the cochlear nerve (CN) were measured and normalized to the ipsilateral facial nerve. Presence of CND was determined by comparison to normative data. Relationships among hearing loss severity, progression, and nerve size were investigated. Results: Cochlear nerve deficiency was present in 26% of children with unilateral SNHL. Its prevalence was higher (48%) in severe to profound SNHL, especially when in infants (100%). Width of the bony cochlear nerve canal (BCNC) correlated strongly with relative CN diameter, density, and area ( R = 0.5); furthermore, a narrow BCNC (<1.7 mm) strongly predicted CND. Severity of hearing loss modestly correlated with nerve size, although significant variability was observed. Progression never occurred unless there were other inner ear malformations, whereas in the non‐CND group, it occurred in 22%. Ophthalmologic abnormalities were very common (67%) in CND children, particularly oculomotor disturbances. Conclusion: Cochlear nerve deficiency is a common cause of unilateral SNHL, particularly in congenital unilateral deafness. Width of the BCNC effectively predicts CND, a finding useful when only computed tomography imaging is available. In an ear with CND, hearing can be expected to remain stable over time. Diagnosis should prompt evaluation by an ophthalmologist.